Defining the Idiot for Africa’s Political Advancement: A Literary Analysis of the Title of Asare’s Ananse in the Land of Idiots - Sanka, Confidence Gbolo; Boateng , Ofori Amanfo; Yakubu, Alhassan; Siaw, Portia Oppong (Journal of Language and Literature Studies, 2024)
The study of literary titles in literature is not new but has become prominent in modern space of literary analysis. People no longer see literary titles as mere appendages with which they identify a literary work, but rather, they look at it as a roadmap to the consumption of the text. A. careful analysis of a literary title as a paratext, provides a clear picture of the narrative and highlights expectations for reading such a text. This is what has made the study of titology relevant in literary studies and literary stylistics.  The objective of this paper is to examine how Asare uses the title: Ananse in the Land of Idiots to portray the characters and their actions in the play; to establish a relationship between the title of the play and its meaning; and to add style with meaning to the overall understanding of the play. The research involved here is qualitative in nature and a close reading method of the primary source and ideas from Genette and other leading critics on the theory of titology are used to study how the title reflects the actions of the characters throughout the play. After a careful analysis of the play in relation to its title, it is revealed that the title does not just identify the drama work. Rather, the title is reflected throughout the plot of the play and adds a metaphorical meaning as well as style to the drama piece. It is concluded established that Asare coins this title stylistically to prompt African leaders and their citizenry about their actions and inactions that facilitate the manipulation of Africa by the West. This implies that a titological approach to literary titles holds the potential of revealing hidden meanings in literary works which are often overlooked.